The Dutch Parelsnoer Institute Cerebrovascular Disease Initiative: a retrospective study of the effects of integrating clinical care and research on costs and quality of care in patients with ischaemic stroke. Issue 8 (27th August 2019) - Mensing, Liselore A; Kappelle, Jaap; Buijs, Julie E; Luijckx, Gert-Jan; Koffijberg, Hendrik; Zielhuis, Gerhard A; Ruigrok, Ynte M
Abstract : Introduction: The Dutch Parelsnoer Institute (PSI) is a collaboration between all university medical centres in which clinical data, imaging and biomaterials are prospectively and uniformly collected for research purposes. The PSI has the ambition to integrate data collected in the context of clinical care with data collected primarily for research purposes. We aimed to evaluate the effects of such integrated registration on costs, efficiency and quality of care. Methods: We retrospectively included patients with cerebral ischaemia of the PSI Cerebrovascular Disease Consortium at two participating centres, one applying an integrated approach on registration of clinical and research data and another with a separate method of registration. We determined the effect of integrated registration on (1) costs and time efficiency using a comparative matched cohort study in 40 patients and (2) quality of the discharge letter in a retrospective cohort study of 400 patients. Results: A shorter registration time (mean difference of −4.6 min, SD 4.7, p=0.001) and a higher quality score of discharge letters (mean difference of 856 points, SD 40.8, p<0.001) was shown for integrated registration compared with separate registration. Integrated registration of data of 300 patients per year would save around €700 salary costs per year. Conclusion: Integrated registration of clinical and research data in patients with cerebral ischaemia is associated with some decrease in salary costs, while at the same time, increased time efficiency and quality of the discharge letter are accomplished. Thus, we recommend integrated registration of clinical and research data in centres with high-volume registration only, due to the initial investments needed to adopt the registration software.